Smart Gate Design and Ship Ticketing with Android Application - Ardhi Fathonisyam Putra Nusantara; Hardian Oktavianto; Lutfi Ali Muharom (Program Studi Teknik Mesin, Universitas Muhammadiyah Surakarta, 2023)
Automatic gate is a development of the digital world that aims to facilitate the lives of residents and reduce errors made by humans. Automation is made to connect humans with technology so that they can advance and develop. In general, the gate serves as a security mechanism. To facilitate human work, the automatic gate system technology is expected to be able to reduce human work, for example when a security guard opens a gate. The technology offered in this paper is a combination of automatic gate systems and sensors with ticketing applications at pioneer ports. This system is expected to be able to facilitate human work with the help of smartphones when using sea transportation at pioneer ports that operate automatically. The main thing that will be discussed in this paper is the gate design for the passenger. The result obtained is an automatic gate that is connected to the ticketing system, both web-based and mobile.